South African Trade Unions in a Time of Adjustment - Wood, Geoffrey (Labour / Le Travail, 2001)
The paper examines South African trade unions from the late apartheid era to the present (2001). Anti-apartheid sanctions and disinvestment affected the labour movement, as did the disastrous miners' strike of 1987. Democratization in the period since has resulted in the lifting of embargoes and the phasing-out of tariffs and state subsidies for industries located near the former bantustans. There has been a growth of public sector unions and private sector unions have also reversed their decline. Generally, the unions are still a force to be reckened with, but the neoliberal turn of the ruling African National Congress, to which the unions are closely linked, poses a serious challenge.